Dampak Stunting Terhadap Kesehatan Anak: Narrative Review - Alifariki, La Ode; Arifiati, Nurce; Rini, Mutia Puspa; Nurseha, Nurseha; Ruwiah, Ruwiah; Indah, Indar (NHM PRESS, 2024)
Stunting in children is a global public health problem that has a significant impact on physical, cognitive and social development. This research analyzed ten studies that examined the relationship between stunting and various aspects of child development, including cognition, motor skills and behavior. The research methods used varied, including cohort studies, case-control studies, and cross-sectional designs, with populations consisting of children under seven years of age in various countries. The results showed that children who were stunted had lower cognitive and motor scores compared to non-stunting children. Additionally, environmental factors, such as maternal education and perinatal conditions, contribute significantly to developmental outcomes. This research emphasizes the need for integrated early intervention to prevent stunting and support children's optimal development. Although this study provides important insights, limitations in design, sample size, and unmeasured variables must be noted. These findings underscore the importance of policies that support child nutrition and health to improve long-term well-being